2015
DOI: 10.4103/1463-1741.155850
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the relationship between noise sensitivity and personality

Abstract: Sensitivity to unwanted sounds is common in general and clinical populations. Noise sensitivity refers to physiological and psychological internal states of an individual that increase the degree of reactivity to noise in general. The current study investigated the relationship between the Big Five personality dimensions and noise sensitivity using the 240-item NEO Personality Inventory (NEO-PI) and 35-item The Noise-Sensitivity-Questionnaire (NoiSeQ) scales, respectively. Overall, the Big Five accounted for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 32 publications
10
53
1
1
Order By: Relevance
“…Our present results corroborate the findings by Shepherd et al [15], producing robust evidence that noise sensitivity can be predicted from extraversion and conscientiousness. Note that emotional stability was not a significant predictor in both of these studies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our present results corroborate the findings by Shepherd et al [15], producing robust evidence that noise sensitivity can be predicted from extraversion and conscientiousness. Note that emotional stability was not a significant predictor in both of these studies.…”
Section: Discussionsupporting
confidence: 83%
“…Noise sensitivity correlated negatively with ratings of Pleasantness, which replicates previous findings [15] and is in line with the definition of the construct. Noise-tolerant participants were biased to rate the restaurant soundscapes as more pleasant.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Authors are starting to acknowledge the limited view on NS that we currently have (see 8). Recently Shepherd et al concluded that delve into the nature and origins of NS is necessary in order to construct a gold standard NS questionnaire and overcome some of the discrepancies in the literature (21). We can only presume that NS has been misspecified in some way as a construct either because it has not been articulated comprehensibly, or because of the non-adequacy of the instruments used to measure it.…”
Section: "Noise Sensitivity" As a Problemmentioning
confidence: 96%